Feed the Common Good- Impact of Social Marketing on Consumer Behaviour - A Study Based in Kolkata - Nath, Soma (International Journal of Engineering and Management Research, 2021)
To keep pace with the fast growing and quickly evolving world of today, marketers have shifted their focus from a profit driven marketing to social marketing. Social marketing is a set of marketing theories which is essentially an adaptation of commercial marketing, and its aim is not to maximize profits but to achieve an impact in the behaviour of the target audience and influence the same for the benefit of the society. Behaviour can be said to be the end point of social marketing.